2016
DOI: 10.1002/ps.4244
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of succinate dehydrogenase inhibitor resistance of Pyrenophora teres in Europe

Abstract: Several target-site mutations in the genes of subunits SDH-B, SDH-C and SDH-D with different impact on SDHI fungicides were detected. The pattern of mutations varied from year to year and between different regions. Strict resistance management strategies are recommended to maintain SDHIs as effective tools for net blotch control, especially in areas with low frequencies of resistant isolates. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
110
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 35 publications
5
110
2
Order By: Relevance
“…DMI resistance is associated with point mutations or overexpression of the enzyme encoded by CYP51 and efflux pump overexpression . Resistance to SDHIs is also caused by mutations in the Sdh genes encoding the subunits of complex II in the respiratory chain . The extent of reduction in sensitivity depends on the chemical structure of the fungicidal molecule, mutation type, and even the stacking of multiple types of mutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMI resistance is associated with point mutations or overexpression of the enzyme encoded by CYP51 and efflux pump overexpression . Resistance to SDHIs is also caused by mutations in the Sdh genes encoding the subunits of complex II in the respiratory chain . The extent of reduction in sensitivity depends on the chemical structure of the fungicidal molecule, mutation type, and even the stacking of multiple types of mutations.…”
Section: Introductionmentioning
confidence: 99%
“…SDHIs are also reported to be under the risk of efficacy loss due to the field isolates which acquired a high level of resistance against this chemical class as a result of a single mutation within the target enzyme (e.g. sdhC ‐H152R in Z. tritici and sdhC ‐G79R in P. teres ) …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the detection of SDHI resistant isolates of Z. tritici obtained from sites in Ireland and the UK [https://cereals.ahdb.org.uk/press/2016/february/12/%20sdhi-fungicide-sensitivity-shift-detected-in-two-uk-septoria-isolates.Aspx (accessed 29 September 2016)] has recently been reported. Furthermore, isolates of Pyrenophora teres (net blotch of barley) resistant to SDHI fungicides have also been detected in several European cereal growing geographies . Cases such as these serve as a constant reminder of the need for continued innovation towards identifying new active chemistries with novel modes of action.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of QoIs, it has been reported that the orthologous amino acid mutations result in similar resistance profiles across different organisms with respect to the strength of resistance; the G143A mutation causes very high level of resistance (the resistance factor RF, [EC 50 of the resistant mutant]/[EC 50 of the wild type], is always greater than 100) to all commercial QoIs in any known cases of more than 20 pathogen species . However, recently some cases of different resistance profiles within the orthologous mutations of different pathogen species were reported in cases of resistance against succinate dehydrogenase inhibitor (SDHI), another important agricultural fungicide class . Considering the unique behavior of metyltetraprole in the G143A mutants of Z. tritici as well as in the F129L mutants of P. teres , its consistency in orthologous mutations in different species should be investigated.…”
Section: Introductionmentioning
confidence: 99%